National seed legislation: Harmonization with international treaties and conventions - Kshetri, B Thapa (Agronomy Journal of Nepal, 2013)
Government of Nepal (GoN) started seed legislation by framing different acts such as Seed Act, 1988 (2045), Seed Regulation 1997(2054) and Seed Policy, 1999 (2056) to regulate seed and seed related issues. Some of these acts have been amended and redrafted according to needs. During this period, GoN, became a contracting party to Convention of Biological Diversity (CBD), 1992 and International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), 2001. It also signed the Cartagena Protocol, 2000 and received the member of WTO in 2004. In these treaties and convention, Nepal has made commitments in international forum to provide plant variety protection with protecting the rights of farmers and related stakeholders on seed to establish sanitary and phyto-sanitary measures for bio-safety. In this context, it is necessary to reframe the national seed legislations in order to remove its present legal complications and to harmonize it with international treaties and conventions. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 138-149 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9016